Re-evaluation of excavation class limits for underground excavations based on new data - Gurocak, Zulfu; Kaya, Ayberk; Kanik, Mustafa; Alemdag, Selcuk (Nature Portfolio, 2025)
Many researchers have proposed empirical excavatability classifications to easily and quickly assess rock masses. These classifications mostly apply to surface excavations, while those for underground excavations are limited. Updating the classifications proposed for underground excavations based on new data is important in terms of eliminating the deficiencies in this regard. This study determined the engineering properties (RMR, Q, GSI), rock material strengths, and in-situ excavation classes of 16 underground rock masses. The new data were compared with excavation classifications from various researchers and empirical classes. The study found that empirical classifications for surface conditions are not applicable for underground. Excavation is more challenging in underground conditions due to stress from overburden. While excavation classes align for good to very good rock masses in both conditions, there is no perfect match for medium, weak, and very weak rock masses for underground. The study suggests that for underground excavation classes (blasting, hammer&blasting, hammer, and digging), both RMR89 and Q values should be used together to differentiate between classes. When using GSI for classification, the Is(50) value of the rock material should also be considered. The sigma cm parameter is the most critical in evaluating rock mass excavatability.
Keywords: Excavatability; Rock mass; Underground excavation; In-situ excavation class; Empirical excavation class; Rock mass strength